Corporate Criminal Responsibility in Land Grabbing Crime - Reumi, Frans; Iskandar PP, Agus; Fatma, Mawarni (PT. Anagata Sembagi Education, 2025)
Land grabbing by corporate entities is a form of structural crime that has a wide impact on land rights, the environment, and social justice in Indonesia. This practice is carried out through various manipulative mechanisms such as falsification of documents, power co-optation, and legal-formal but socially illegitimate land tenure. Unfortunately, the national criminal law framework has not been fully able to reach the complexity of these corporate crimes. This study aims to analyze corporate criminal liability in agrarian crimes with a normative juridical approach through a study of the Criminal Code, UUPA, and PPLH Law. The theory of corporate criminal liability and the concept of piercing the corporate veil are used to connect structural errors in the corporate body with criminal offenses that occur. The results of the study show that there are normative gaps and weaknesses in law enforcement, especially in making corporations the subject of crime effectively. Therefore, it is necessary to integrate criminal, agrarian, and environmental law, as well as the establishment of special criminal norms that are lex specialis in agrarian law. The novelty of this research lies in the offer of reconstruction of corporate criminal law enforcement based on substantive justice. This reform is expected to be able to encourage agrarian sovereignty and the protection of people's constitutional rights